Efektivitas Program Dana Desa Dalam Peningkatan Kesejahteraan Masyarakat Desa Sukarami Kecamatan Kaur Tengah Kabupaten Kaur Tahun 2025 - Astrianai, Ramita; Dwisnu, Erlian; Solihin, Muhammad (Jurnal Stia Bengkulu : Committe to Administration for Education Quality, 2026)
This study aims to analyze the effectiveness of the Village Fund Program in the development of farm road infrastructure in Sukarami Village, Kaur Tengah District, Kaur Regency. The research focuses on five main aspects: (1) program planning, (2) program implementation, (3) community participation, (4) transparency and accountability, and (5) the program’s impact on community welfare. This research employed a descriptive qualitative method, using in-depth interviews, field observations, and documentation for data collection. The informants consisted of the Village Head, the Head of the Village Consultative Body (BPD), community leaders, and 20 villagers who benefited directly from the program. Data were analyzed using the interactive model of Miles and Huberman (1994) through three main stages: data reduction, data display, and conclusion drawing/verification. The results showed that the implementation of the Village Fund Program for farm road construction in Sukarami Village was quite effective. The construction of a 1,200-meter concrete farm road significantly improved accessibility, reduced transportation time and costs by up to 25%, and enhanced agricultural productivity. However, community participation in planning and supervision remains limited, and several obstacles were identified, such as delayed fund disbursement, limited administrative capacity, and insufficient transparency and public dissemination of information. In conclusion, the Village Fund Program has made a significant contribution to improving farmers’ welfare, particularly by enhancing agricultural access roads. Nonetheless, its overall effectiveness can be further improved through increased community involvement, stronger accountability mechanisms, and sustainable infrastructure maintenance.